Estimated correlations of ultrasound carcass measurements and physical-chemical components of Santa Ines sheep meat - André Torres Geraldo; Jonhny de Azevedo Maia Júnior; Ricardo Lopes Dias da Costa; Renato Travassos Beltrame; Adriano Azevedo; Alexandre Cristiano Santos Júnior; Aparecida Fatima Madella-Oliveira; Celia Raquel Quirino (Acta Scientiarum. Animal Sciences, 2023)
The evaluation of the carcass composition of livestock generates relevant information on the quality and final yield of the meat products. The objective of this work was to evaluate correlations the ultrasound measurements in vivo of the Longissimus lumborum with the physical-chemical components of one-year-old Santa Ines sheep bred in extensive systems. The ultrasound evaluation was performed of the rib eye area (USrea), loin depth (USld), loin width (USlw) and subcutaneous fat thickness (USsft). After slaughter, meat cuts were weighed and carcass yield was calculated. The 12th rib on the left side was separated from the carcass and dissected, after which individual bones, muscles and fat were separated and weighed. The components were regrouped, ground and collected for centesimal evaluation. Significant positive correlations (p < 0.05) were found between the ultrasound measurements and meat metrics, except for the loin length, which had low correlation. Significant correlations (p < 0.05) were found between muscles and the measurements of USld, USrea and USsft. The correlations (p < 0.05) between the bones and USld and USrea were negative and significant. USsft presented correlation (p < 0.05) with carcass yield. Thus, the ultrasound measurements associated with the Longissimus lumborum could constitute a valuable tool for evaluating the physical-chemical components and carcass of one-year-old Santa Inês sheep created in extensive systems.